Executive function and attention profiles in preschool and elementary school children with autism spectrum disorders or ADHD. (July 2014) - Sinzig, Judith; Vinzelberg, Isabella; Evers, Dagmar; Lehmkuhl, Gerd
Abstract : Both autism spectrum disorder (ASD) and attention deficit/hyperactivity disorder (ADHD) show executive function and attention problems. By now, these are well described in school children and adolescents, but not in preschool or elementary school children. The goal of this study was to compare the neuropsychological profiles of executive and attention functions in an ADHD, an ASD, and a typically-developing group. Eighty-five children aged 4–9 years old with ADHD ( n  = 30) or ASD ( n  = 26) and healthy children ( n  = 29) were included consecutively. Psychopathology was evaluated using the KIDDIE-SADS, the Child Behaviour Checklist (CBCL), and symptom checklists for ADHD according to DSM-IV . Assessment of neuropsychological functioning included tasks from the Amsterdam Neuropsychological Tasks (ANT), namely, inhibition (GoNoGo), flexibility (shifting attentional set visual), and sustained attention (sustained attention objects). A MANOVA with age and IQ as covariates revealed statistically significant group effects for the variable 'flexibility errors compatible'. Effect sizes showed clear deficits of children with ASD and ADHD in inhibition and, furthermore, impairments in sustained attention in ASD children. Pearson correlations revealed associations between social problems and aggressive behaviour with all three tasks in the ADHD group and between thought problems and sustained attention in the ASD group. Our hypothesis was partly confirmed as ADHD children showed more deficits in inhibition tasks than healthy children. However, there was no evidence that children with ASD have a specific profile in comparison to ADHD children.